Characterization of the beta-lactamases of six species of Legionella. - Marre, R (1982)
The beta-lactamases of six Legionella species were characterized by isoelectric focusing, gel filtration, and substrate profiles. Fifteen strains of L. bozemanii, L. dumoffii, L. gormanii, L. longbeachae, and L. pneumophila produced beta-lactamases active against nitrocefin. L. micdadei enzymes previously reported to be beta-lactamase negative caused a very slow pH-dependent breakdown of nitrocefin and degraded penicillin G at high substrate concentrations. The bioassay revealed predominantly penicillinase activity for all species except L. micdadei, which had no activity in this assay. The apparent molecular weights of enzymes of L. bozemanii, L. gormanii, and L. pneumophila were in the range of 15,000 to 32,000, and those of L. micdadei and L. longbeachae were greater than 250,000. The isoelectric focusing of extracts of Legionella strains in polyacrylamide gels showed beta-lactamase types specific for species (L. bozemanii, L. gormanii, and L. pneumophila) and serotype (L. pneumophila). It demonstrated four different beta-lactamase types in L. pneumophila and revealed close relationships among L. pneumophila serotypes 1, 3, and 6. L. pneumophila enzymes formed band patterns only in polyacrylamide gels containing 6 M urea, whereas L. dumoffii and L. longbeachae enzymes did not form bands in any of the gels. None of the band patterns resembled those of known plasmid-mediated beta-lactamases. These experiments suggest that isoelectric focusing of chromosomal beta-lactamases may be a valuable tool for taxonomic studies.